Numerical thermodynamic analysis of alloys for plasma electronics and advanced technologies - Kuzenov, V.V.; Ryzhkov, S.V.; Shumaev, V.V. (Вопросы атомной науки и техники, 2015)
Thermodynamic properties (pressure, specific internal energy and entropy) of the ionized gas mixture are obtained on the basis of the Thomas-Fermi theory and Saha model. The calculations was made for the lithium-indium alloy (Li + 10% In), which has various applications in plasma electronics and technology.